LECTURER SOFT-SKILLS COMPETENCIES DEVELOPMENT MODEL: SUPPORTING LEARNING IN DIGITAL ERA AND â€œKAMPUS MERDEKAâ€ PROGRAM - Maximus Gorky Sembiring; Yogaprasta Adi Nugraha (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Globalization has initiated the competition in many sectors and has become a necessity. Advances in information and communication technology combined with the industrial revolution added to the frenzy of the situation. All sectors were obliged to make the related adjustments. The Covid-19 pandemic immediately made competition and uncertainty compound. Education has several types and levels, one of which is higher education. One of the determinants of university accomplishment is lecturers. The quality of human resources can be seen from the competence of hard skills and soft skills. Universities are required to redirect human resources to obtain the best quality of education. Universities are required to improve the quality of education management oriented to the development of soft skills. This study uses a quantitative approach with the help of structural equation modelling (SEM). A total of 133 lecturers were taken as the research sample. The results show that of the six soft skills studied (critical thinking, creativity, initiative, teamwork, and networking) two main variables are determined. They are initiative and networking ability. In relation to learning in the digital era and the â€œKampus Merdekaâ€ program, this study suggests the importance of lecturers always taking the initiative and utilizing the ability to initiate. Besides, lecturers are advised to conduct and maintain networks to be able to prepare human resources, especially amidst the uncertainty.